Worrisome Features for Intraductal Papillary Mucinous Neoplasm: Should We be Worried? - Lorenzo Dioscoridi (Pancreas, 2022)
Although worrisome features represent an indication to perform endoscopic ultrasound study, recent studies have showed that these conditions are not strictly related to high risk of malignancy. Pancreatic resection for worrisome imaging features often demonstrates pathology consistent with low-grade dysplasia. Worrisome features should be considered as indicators of mostly low-grade dysplasia. High-risk stigmata are more consistent for diagnosis of malignant lesions.